Redefining the Scope of Ayurveda in Cardiology - Madhavan, Jithesh (Asian Journal of Pharmaceutical Research and Development, 2018)
Cardiovascular diseases (CVDs) have now become the leading cause of mortality or even morbidity in India. According to the World Health Organization, cardiovascular disease causes 12 million deaths in the world each year. Even with all the advancements in medicine, the management of CVD’s are yet to be redefined. Ayurveda proposes a different understanding to etiopathogenesis of such conditions and subsequent healthcare, in the context of hrdroga. Latest researches in Ayurveda have given a new hope in CVDs, the curative as well as preventive aspects. With the emergence of increasing number of cardiac problems from the young age itself, it is the time to explore various options available in the alternative areas of medicine. Herbs and dietary supplements can have significant role in preventive cardiology as well as per published studies. Equivalent is the management of associative psychological contributors. In this article, research works of medicinal plants useful in cardiology are described with special emphasis on rasona, arjuna, guggulu, amalaki and gokshura. This work emphasises the scope of such practice so as to popularize the options available in Ayurvedic literature.